The Secret Royals : spying and the crown, from Victoria to Diana - Aldrich, Richard J. (Richard James), 1961-; Cormac, Rory (London : Atlantic Books, 2021)
"For the first time, The Secret Royals uncovers the remarkable relationship between the Royal Family and the intelligence community, from the reign of Queen Victoria to the death of Princess Diana. It shows how the British secret services grew out of persistent attempts to assassinate Victoria and then operated on a private and informal basis, drawing on close personal relationships between senior spies, the aristocracy, and the monarchy. This reached its zenith after the murder of the Romanovs and the Russian revolution when, fearing a similar revolt in Britain, King George V considered using private networks to provide intelligence on the loyalty of the armed forces - and of the broader population."--Provided by the publisher
Includes bibliographical references and index.
Keywords: Victoria, -- Queen of Great Britain, -- 1819-1901.; Windsor, House of; Intelligence service -- Great Britain -- History; Great Britain -- History -- Victoria, 1837-1901.; Great Britain -- History -- Elizabeth II, 1952-2022.